Understanding Hydrogen Passivation Mechanism in poly-Si Passivating Contacts via SixNy Composition: Insights From Effusion Studies - Suchismita Mitra; Dirk Steyn; William Nemeth; Sumit Agarwal; Paul Stradins (SiliconPV Conference Proceedings)
Tunnel Oxide Passivated Contact (TOPCon) cell performance relies significantly on hydrogen for its passivation of defects. In this paper, we discuss the temperature dependent effusion of hydrogen from the silicon nitride (SixNy) layers deposited on top of poly-Si/SiO2 passivated contacts. Silicon content in SixNywas varied by silane/ammonia flow ratio. FTIR shows significant N-H stretching & bending peaks for nitrogen-rich SixNy layer compared to silicon-rich SixNy layer, and few Si-H bonds compared to silicon-rich SixNy. During effusion, the N-H bonds in N-rich SixNy layer break to provide H2 , NH3 and N2, resulting in stoichiometry change. Negligible effusion of nitrogen occurs for Si-rich SixNylayers. Next, we investigate the mechanism of hydrogen passivation on symmetrical i-poly-Si/SiO2/i-poly-Si structures with different hydrogenating layers namely Si-rich SixNy , Al2O3 and a stack of Al2O3/SixNy, and conclude that a thin 15nm Al2O3 enables the best passivation. We also discuss the possibility of H diffusion in molecular H2 form, most suitable for SiO2 interface passivation, while the atomic hydrogen enables both passivation and de-passivation of interface dangling bonds.